Eco-Design and Energy Saving Concepts for the Agricultural Commercial Fringe Communities in Western Thailand - Pastraporn Thipayasothorn; Rachadakorn Phonpakdee; Saravanee Phuengpunum; Aumamporn Pechsinjon (My University, 2018)
These The purpose of this study was to develop planning for the communities along the agricultural – commercial fringe in the Special Economic Zones of western Thailand corresponding to the area’s physical environment, activities and commuting patterns. In order to fulfill the purpose, this study has analyzed the significant activities and commuting patterns of the communities along the particular fringe area in the Special Economic Zones of 5 western provinces as well as the opinions towards community planning given by 400 residents living in the certain areas. The findings indicated that the establishment of an economic development plan for the development of commuting routes of the Special Economic Zone in the western part of Thailand is very appropriate. The plan will ultimately enhance economic development by optimizing all commuting routes, activities, and resources that originally exists in the local environment and economically impact all community throughout every region of Thailand.
Keywords: Special economic zone; Socioeconomic Development in Asia